Acehnese Characteristics in Ratéb Doda Idi: The Sustainability of Social Values through Parents’ Message - Yanti, Nurlayli; Nushur, Rizki Dhian; Anwar, Humaira (Universitas Negeri Semarang, 2024)
Ratéb doda idi is an oral tradition of lulling children to sleep in Acehnese society by exploring the values of education and efforts to build children’s character from an early age. Ratéb doda idi is a contextual answer to the problem of the need for value socialization or moral education for Acehnese children. This research aims to describe the characteristics that Acehnese transfer through ratéb doda idi which can provide the child with basic necessities for his future. This research used a qualitative approach research method which is based on data obtained in the field and then strengthened by literature study. This research took place in Aceh, specifically in Aceh Besar, especially the community at three points, namely Indrapuri, Indrapatra, and Indrapurwa. Based on the research results, there are several types of characters that are starting to be instilled through ratéb doda idi. These characters are religious, tolerance, hard work, national spirit and nationalism, social care, and responsible character.